The relationship between the unsteady fluid force and the pressure distribution around the foot during breaststroke kicking - Tsunokawa, T.; Sengoku, Y.; Tsubakimoto, S.; Takagi, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2015)
The purpose of this study was to identify the characteristics of the pressure distribution around the foot during breaststroke kicking and the relationship between the fluid force and the pressure distribution by comparison among different swimmers. Eight male elite swimmers, whose specialties were breaststroke and individual medley, participated in this study. In trials conducted in a water channel, swimmers performed breaststroke kicking for ten seconds at individually controlled flow velocity determined in prior time trials without upper limb motion. During the trials, eight pressure sensors were attached to the left foot to measure the pressure distribution around the foot, and the fluid forces were estimated using the procedure reported by Tsunokawa et al. (2012). To identify the relationship between the fluid force and the pressure distribution around the foot, raw pressure values and the pressure differences between the plantar side and the dorsal side were indicated. This revealed significant differences in the absolute values of pressure between the plantar and dorsal sides (p<0.01), except for the area around the fifth toe. The dorsal side pressure for high-level swimmers decreased to about -25 kN/m2, and that for slightly low-level swimmers decreased to about -12 kN/m2. These results suggest that a decrease of dorsal side pressure is closely related to an increase in the fluid force acting on the foot, and that the kicking motions of high-level swimmers create a rapid decrease of dorsal side pressure. Furthermore, unsteady vortex-like flow is closely related to an increase in the fluid force acting on the foot. Therefore, swimmers and coaches should be aware of these influences of unsteady fluid forces.